380 Effects of estradiol benzoate on reproductive characteristics in beef cows. (5th December 2019) - Dysart, Lacey M; Lemley, Caleb O; Messman, Riley; Larson, Jamie E
Abstract: Ovulation prompted by exogenous GnRH may cause the release of sub-mature oocytes and lead to decreased pregnancy rates. Inclusion of estradiol benzoate (EB) has improved pregnancy rates. The objective was to determine if EB affects blood perfusion of follicles, CL, or uterus, concentrations of estradiol, or incidence of standing estrus. Forty-seven suckled beef cows were synchronized (GnRH+CIDR on d -9, PGF2a+CIDR removal on d -2, expected estrus=d 0). On d -1, 24 of 47 cows received an injection of EB (1mg/2mL) while the other 23 remained as a control group. Ovaries were evaluated via Doppler ultrasonography on d -1, 0, 6, 14, and 21. A laser Doppler probe was used to measure blood perfusion of the uterus on d -1, 0, and 6. Only cows that exhibited estrus (n = 29) were evaluated on d 14 and 21. Images were analyzed via ImageJ software to determine mean area of perfusion. Blood samples were collected on d -1 and 0 and analyzed for concentrations of estradiol using RIA. Using SAS, MIXED and FREQ were used to determine the influence of treatment on blood perfusion and estradiol, and incidence of standing estrus, respectively. Treatment with EB increased (P < 0.001) the number of cows exhibiting standing estrus compared to control (21/24 vs 8/23, respectively). Treatment of EB did not (P > 0.10) alter blood perfusion of the follicles or uterus on any day or perfusion of the CL on d 6. However, EB increased (P < 0.036) the size of the CL on d 14 (25.06±1.7 vs 6.06±3.7) and tended (P < 0.097) to increase the size of the CL on d 21. Treatment of EB increased (P < 0.003) concentrations of estradiol on d 0 compared to control (21.35±4.49 vs 9.44±4.61 pg/mL). In conclusion, treatment with EB may play a role in changing the CL after ovulation.